2002
DOI: 10.1073/pnas.202331299
|View full text |Cite
|
Sign up to set email alerts
|

FlgM gains structure in living cells

Abstract: Intrinsically disordered proteins such as FlgM play important roles in biology, but little is known about their structure in cells. We use NMR to show that FlgM gains structure inside living Escherichia coli cells and under physiologically relevant conditions in vitro, i.e., in solutions containing high concentrations (>400 g͞liter) of glucose, BSA, or ovalbumin. Structure formation represents solute-induced changes in the equilibrium between the structured and disordered forms of FlgM. The results provide ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
286
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(302 citation statements)
references
References 29 publications
9
286
1
6
Order By: Relevance
“…A pioneering study has recently demonstrated that an intrinsically disordered protein region is in fact structured in living cells (73). FlgM, a 97-residue protein from Salmonella typhimurium, which regulates flagellar synthesis by binding the transcription factor 28 , is fully unstructured in vitro (74).…”
Section: Resultsmentioning
confidence: 99%
“…A pioneering study has recently demonstrated that an intrinsically disordered protein region is in fact structured in living cells (73). FlgM, a 97-residue protein from Salmonella typhimurium, which regulates flagellar synthesis by binding the transcription factor 28 , is fully unstructured in vitro (74).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, HSQC spectra of disordered proteins such as FlgM and α-synuclein are easier to observe in cells (Dedmon et al 2002;). This increased detectability probably arises because disordered proteins possess much more internal motion than do globular proteins, and this internal motion is less affected by attractive interactions with other cellular macromolecules.…”
Section: Crowding and Assemblymentioning
confidence: 99%
“…These observations support the existence of protein disorder inside the cell. The existence of intracellular protein disorder recently received additional support when FlgM, previously shown to be an intrinsically disordered protein 14,15 , was found by in vivo NMR experiments to gain some structure for only part of the molecule when in the cell, with about half of the protein remaining in the intrinsically disordered form 16 .…”
Section: Introductionmentioning
confidence: 99%